Coagulation Activation by MC28 Fibrosarcoma Cells Facilitates Lung Tumor Formation - Francis, J L; Amirkhosravi, M (Thrombosis and Haemostasis, 1995)
Tumor cells interact with the hemostatic system in various ways and may thus influence malignant growth and spread. MC28 fibrosarcoma cells possess a potent procoagulant activity (PCA) and form lung tumors following intravenous injection. The aim of this work was to study the relationship between PCA, intravascular coagulation and lung seeding in the MC28 model. MC28 cells were injected into control, warfarinized and heparinized hooded Lister rats. Coagulation changes were monitored by thromboelastography (TEG) and Sonoclot™ analysis (SA), lung fibrin formation by light and electron microscopy, tumor seeding by macroscopic counting and tumor cell and platelet deposition in the lungs by radiolabelling. PCA was measured by chromogenic assay. MC28 PCA was characterized as a tissue factorfactor VIIa complex that probably arose during cell culture or disaggregation of solid tumors. Injection of tumor cells caused marked coagulopathy and was rapidly (within 30 min) followed by fibrin deposition in the lungs and accumulation of radiolabelled platelets. Heparin and warfarin significantly reduced lung seeding (p <0.001) and reduced retention of radiolabelled tumor cells in the pulmonary circulation (p <0.01). Inhibition of cellular PCA by prior treatment with con- canavalin A markedly reduced intravascular coagulation and lung seeding.We conclude that MC28 cells cause intravascular coagulation as a direct result of their procoagulant activity. The data suggest that tumor cells form complexes with platelets and fibrin which are retained in the lungs long enough for extravasation and seeding to occur.Anticoagulation reduces tumor cell-platelet-fibrin complex formation, decreasing the time spent in the lungs and thereby reduces seeding. Thus, the antitumor effect of warfarin, at least in the MC28 model, is due to its anticoagulant action.